2015
DOI: 10.1007/s12010-015-1909-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drought Stress on Total Phenolic, Lipid Peroxidation, and Antioxidant Activity of Achillea Species

Abstract: The changes in total phenolic content (TPC), total flavonoid content (TFC), proline, malondialdehyde (MDA), H2O2, and antioxidant activity were assessed based on three model systems in three Achillea species (Achillea millefolium, A. nobilis, and A. filipendulina) growing under four irrigation regimes, including 100% FC (field capacity as normal irrigation) 75% FC (low stress), 50% FC (moderate stress), and 25% FC (severe stress) conditions. The highest TPC (47.13 mg tannic acid/g DW) and TFC (20.86 mg quercet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(124 citation statements)
references
References 50 publications
10
98
0
3
Order By: Relevance
“…The results reported by Ashraf et al [38] on the DPPH contents of P. abrotanoides leaves and stems were not comparable with ours, probably due to differences in standards and experimental conditions. [39] However, our results are confirmed by those obtained for seven Salvia species by Aghaei Jeshvaghani et al [36] who reported IC 50 values in the range of 198 lg/ml in S. virgata to 1810 lg/ml in S. persica. It might be concluded that some Salvia species recorded antioxidant activities within the range obtained for the Perovskia populations investigated in the present study while others exhibited lower capacities.…”
Section: Antioxidant Capacitysupporting
confidence: 91%
See 1 more Smart Citation
“…The results reported by Ashraf et al [38] on the DPPH contents of P. abrotanoides leaves and stems were not comparable with ours, probably due to differences in standards and experimental conditions. [39] However, our results are confirmed by those obtained for seven Salvia species by Aghaei Jeshvaghani et al [36] who reported IC 50 values in the range of 198 lg/ml in S. virgata to 1810 lg/ml in S. persica. It might be concluded that some Salvia species recorded antioxidant activities within the range obtained for the Perovskia populations investigated in the present study while others exhibited lower capacities.…”
Section: Antioxidant Capacitysupporting
confidence: 91%
“…on the DPPH contents of P . abrotanoides leaves and stems were not comparable with ours, probably due to differences in standards and experimental conditions . However, our results are confirmed by those obtained for seven Salvia species by Aghaei Jeshvaghani et al .…”
Section: Resultssupporting
confidence: 50%
“…Phenolic compounds, which are another class of metabolites that accumulate in plants upon drought stress (Gharibi et al ., ), also showed differences between the untreated and endophyte‐treated plants. Levels of caffeic and ferulic acids increased in the leaves of uninoculated plants under stress, whereas S. implicatum‐ infected plants accumulated moderate levels of both compounds and A. sclerotigenum ‐treated plants did not show a significant difference in the amounts of these metabolites under optimal or drought conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds, which are another class of metabolites that accumulate in plants upon drought stress (Gharibi et al, 2016), also showed differences between the untreated Combined sequences of the ITS regions and ef1-α genes of the two isolates were used in a BLAST search the NCBI nonredundant fungal database. A maximum likelihood phylogenetic tree of the most closely related sequences was constructed by the neighbour-joining method.…”
Section: Stress Indicators Are Modified In Endophyte-treated Plantsmentioning
confidence: 99%
“…As a result, DHA-rich oil is easily oxidized and loses its physiological functions. In addition, this oxidized oil can produce a number of harmful substances in the human body, and its peculiar smell is not acceptable to most consumers [6]. Thus, a stable antioxidative process must be established to maintain the original physiological and storage properties of PUFAs.…”
Section: Introductionmentioning
confidence: 99%